1981
DOI: 10.1159/000198598
|View full text |Cite
|
Sign up to set email alerts
|

Bile Reflux Esophagitis

Abstract: This study was designed to determine the relative contribution of acid and/or duodenal contents on development of reflux esophagitis in the rat. Gross and microscopic changes in the esophageal mucosa at 10, 15, 30, and 60 days were recorded in sham-operated animals and in two experimental groups. One study group had a transsection of the esopha-gogastric junction (model I), and the other a total gastrectomy (model II). Bowel continuity was reestablished by esophagojejunal anastomosis. Subgroups of both animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Since Helsingen's experiments (1959;1960), many experiments attempting to elucidate the pathogenesis of reflux esophagitis have been performed (Henderson et al, 1972;Siroos et al, 197.5;Salmon and Hem, 1981;Mud et al, 1982;Lehnert et al, 1983). Levrat et al (1962) concluded that reflux esophagitis develops when duodenal contents regurgitate into the esophagus.…”
Section: Referencesmentioning
confidence: 99%
“…Since Helsingen's experiments (1959;1960), many experiments attempting to elucidate the pathogenesis of reflux esophagitis have been performed (Henderson et al, 1972;Siroos et al, 197.5;Salmon and Hem, 1981;Mud et al, 1982;Lehnert et al, 1983). Levrat et al (1962) concluded that reflux esophagitis develops when duodenal contents regurgitate into the esophagus.…”
Section: Referencesmentioning
confidence: 99%